Effective marketing video application by using geotagged Twitter's status metadata - Limanto, Adrian Samuel *; Lee, Yunli * (2011)
Recently, social networking sites with the capability of micro-blogging have earned many attentions from mobile audience as a favorite way of real-time blogging. People may update their status or even sharing photographs using their mobile phones. Micro-blogging sites, such as Twitter has the capability to add geographical location information using global positioning system. In this paper, we proposed a more effective way of marketing events or products based on user?s location metadata. With the aid of software technology and information system, we proposed to develop an application that will identify the user?s location and send videos that are related to the user current location. Relevant videos will be sent to the user?s mobile phone so that user is aware if there is any promotion or event around them. The videos will be sent through MMS or microblogging?s site status update from the promoters to the user?s phone. In this paper, we describe of how this proposed work can be applied in the real-world environment and also future improvements of this application.